HLA – B association in psoriasis - Ashwin Anandan; Krishnamoorthy Radhakrishnan; Ravindra Prasad Thokala; Vinod Kumar Panicker; Murugan Sundaram (International Journal of Medical Research and Review, 2016)
Background: Psoriasis is a common skin disorder with prevalence varying from 0% to 11.8% in different population. HLA association with psoriasis is well established with very little information about Indian Population.Aim: To determine the HLA-B pattern and its association in psoriasis patients.Materials and Methods: Fifty cases and 50 controls were enrolled in the study. HLA-B typing was done by PCR-SSP method and the results was analyzed and interpreted.Results: The alleles that were found in higher frequency in the cases than in the controls were – HLA-B*35 (34%), HLA-B*15 (26%), HLA-B*40 (26%) and HLA-B*18(14%).Conclusion: HLA-B*18 and HLA-B*40 show a strong association with psoriasis.